Meneliti Peran UMKM Dalam Peningkatan Ekspor: Suatu Analisis - Viko Ramadani; Keisha Wulandari (Lembaga Pengembangan Kinerja Dosen, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the economy, although their performance is still hampered by various obstacles and lack of capital support. This research analyzes the contribution of MSMEs to exports by considering these factors. There are three main reasons why attention to MSMEs is important. First, MSMEs act as a survival strategy in the midst of an economic downturn. Second, the tendency of MSMEs to absorb a lot of labor makes them the driving force of the local economy. Third, the role of MSMEs in reducing poverty levels and creating equal distribution of income in society.